Resiliency and empowerment of the HIV community in Nepal during Covid-19: equity and gender-based lenses - Dhungel, Rita (My University, 2020)
This paper examines the voices and experiences of one of the marginalised communities, Women Living with HIV (WLWH) in Nepal at the intersections of COVID-19 and structural inequality and injustice. The overarching goal of this paper is to identify impact and implications of COVID-19 on the HIV community with a focus on factors that further escalate their vulnerability to socio-economic marginalisation and mental and psychological challenges. This study was guided by Interpretative Phenomenology Analysis (IPA). For the purpose of this study two focus groups and semi structured interviews were virtually conducted with 11 Women Living with HIV (WLWH) in Kathmandu, Nepal, using a qualitative paradigm. The Psychosocial Pyramid was used to analyse the data, and through thematic analysis the data was coded and categorised from equity and human rights lenses. This community-based study uncovered that the WLWH experience of COVID-19 was further compounded by gender oppression. At a national level, the Government of Nepal imposed a lockdown as an appropriate measure to limit the spread of COVID-19, but this response failed to adequately meet the needs of marginalized populations, especially WLWH, due to a number of restrictions of the lockdown. The emergency relief program, mainly food hamper, was introduced as part of the lockdown response that did not even maintain the privacy of WLWH. It is imperative for the Government to acknowledge the challenges and vulnerability that WLWH experience from COVID-19, which are discussed in the results section, and develop integrative approaches, programs and policies in addressing these issues in the second wave of COVID and post-COVID-19.
Keywords: HIV community; empowerment; COVID-19; human rights; equity